Sustainable air travel consumption behavior of Generation Z in Vietnam: Developing a theoretical measurement framework - Ly, Long; Phạm, Tung, M. (Edelweiss Applied Science and Technology, 2025)
This study aims to formulate and empirically test a theoretical framework elucidating sustainable air travel consumption behavior among Generation Z in Vietnam. A quantitative survey was conducted, yielding 752 valid responses from Vietnamese Generation Z travelers. The analysis employed partial least squares structural equation modeling (PLS-SEM) to examine the relationships between green consumption values, environmental concern, personal norms, willingness to sacrifice, behavioral intention, and actual sustainable behavior, with economic constraints serving as a moderating variable. The findings indicate that green consumption values significantly enhance environmental awareness and perspectives on sustainable air travel. Personal norms strongly predict the propensity to sacrifice, while attitude and willingness to sacrifice positively influence behavioral intention. Economic restrictions negatively impact the relationship between behavioral intention and actual sustainable conduct. The integrated framework, combining the Value–Belief–Norm, Theory of Planned Behavior, and Motivation–Opportunity–Ability models, effectively explains the attitude–behavior gap in sustainable air travel. Airlines and governments should strengthen value-based communication, reduce economic barriers, and enhance transparency to promote sustainable flying options among young consumers.